PENERAPAN TATA TERTIB SEKOLAH DALAM MENGATASI PELANGGARAN SISWA DI MTS NEGERI SUNGAI PINYUH - Ulani, Desti; Salim, Izhar; Imran, Imran (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract: Is this thesis entitled : the implementation of school rules by teacher in overcoming student violation of MTs Negeri 1 Sungai Pinyuh. The general problem of this research is how is the implementation of school rules by teacher overcoming student violation of MTs Negeri 1 Sungai Pinyuh. The problem in this research is how the implementation of school rules by teacher in overcoming student violation of MTs Negeri 1 Sungai Pinyuh. The scope of this research includes the implementation of school rules by teacher overcoming student violation of MTs Negeri 1 Sungai Pinyuh. This research uses qualitative approach with the descriptive method. The techniques of data collection are observation structured interview field note and archives. The recearch result shows that the implementation of school rules by teacher consist of some stages. It is introduces the rules to students and their parents. There is a supervision to control the rules where the headmaster, vice chairman of student, vice chair of curriculum and counseling teacher doing meeting once a month to evaluate the school rules to be revised the once in six months.Keywords: Implementation, School Rules, Teacher, MTs Negeri 1 Sungai Pinyuh